(untitled) (Al-Qamar, 2025)
This article undertakes a critical and comparative study of the concept of the soul in Buddhism and Islam, highlighting both convergences and divergences between the two traditions. The study reveals that while Buddhism largely denies the existence of an eternal and independent soul (Atman), it upholds the doctrines of karma, rebirth, and nirvana as central to human destiny. According to Buddhist thought, the continuity of existence is explained not through an enduring soul but through the causal chain of deeds, where past actions shape future lives, and ultimate liberation (nirvana) signifies freedom from the cycle of rebirth and suffering. In contrast, Islam affirms the soul as a divinely created, subtle, and enduring entity that governs life and remains after death, accountable for its deeds in the Hereafter. The Qur’an and Hadith emphasize the soul’s transcendental nature, its connection to divine command, and its role in eternal salvation or punishment. The paper further notes similarities in ethical teachings—such as self-purification, moral discipline, and detachment from worldly desires—yet underscores fundamental differences regarding theism, afterlife, and salvation. It concludes that while both religions aim at human moral refinement and ultimate liberation, their metaphysical foundations diverge significantly, with Islam grounding the soul’s reality in divine revelation and accountability, and Buddhism construing liberation through self-realization and negation of soul’s permanence.